CALLUS INDUCTION STUDIES IN SUNFLOWER (HELIANTHUS ANNUUS L.) - SANKAR, P. DEEPA; SUBBRARAMAN, N.; HEMAVATHY, A. THANGA (Annals of Agricultural Research, 2014)
Germinating seed, hypocotyl, stem bits and cotyledon from germinating seeds were chosen as explants for callus induction in the genotypes CO 2, CO 4, Modem, TCSH 1 and P 6460. Efficient callus indication was observed only from cotyledonary explants tested on MS + 2,4-D 2mg1-1+kinetin 0.5mgl-1 , MS +2,4-D 3 mgl-1 +kinetin 0.5mgl-1 and MS + 2,4-D 2mgl-1 media recorded the lowest callus induction days, the highest per cent callus induction and the highest callus weight. Callus can be best induced in cotyledonary explants of sunflower in MS + 2, 4-D 2 mgl-1 + kinetin 0.25gl-1 + CH 1gl-1 media utilizing genotype CO 4 followed by P 6460.